Study of Some Biochemical Parameters in Iraqi Children with Acute Lymphoblastic Leukemia (Baghdad Science Journal, 2015)
Leukemia or cancer of the blood is the most common childhood cancer, Acute lymphoblastic leukemia (ALL), is the most common form of leukemia that occurs in children. It is characterized by the presence of too many immature white blood cells in the child’s blood and bone marrow, Acute lymphoblastic leukemia can occur in adults too, treatment is different for children. Children with ALL develop symptoms related to infiltration of blasts in the bone marrow, lymphoid system, and extramedullary sites, such as the central nervous system (CNS). Common constitutional indications consist of fatigue (50%), pallor (25%), fever (60%), and weight loss (26%). Infiltration of blast cells in the marrow cavity and periosteum often lead to bone pain (23%) and disturbance of normal hematopoiesis. Thrombocytopenia with platelet counts less than 100,000 are seen in approximately 75% of patients. About 40% of patients with childhood ALL present with hemoglobin levels less than 7 g/dL. Although leukocyte counts greater than 50,000/mm3 occur in 20% of cases, neutropenia defined as an absolute neutrophil count less than 500 is common at presentation and is associated with an increased risk of infection. The aim of this study was to investigate the differentiations in some biochemical parameters (Hb, PCV, total serum proteins Aspartate amino transferase(AST), Alanin amino transferase (ALT), and Malondialdehyde (MDA) in blood which can be conceder as a marker of ALL. Samples were collected from 50 patients (between 1-16 years old) diagnosed with ALL after one month treatment with induction therapy, compared with 30 control samples taken from healthy persons at the same age . The ALT and MDA showed a significant increase p < 0.001 and p